Odpowiedź:
1.
a)
(2,75 + 1 5/6) : 5 = (2 3/4 + 1 5/6) * 1/5 = (2 9/12 + 1 10/12) * 1/5 = 3 19/12 * 1/5 =
= 55/12 * 1/5 = 11/12
b)
1,9 - 0,9 * 1/3 = 1,9 - 9/10 * 1/3 = 1,9 - 3/10 = 1,9 - 0,3 = 1,6
2.
a)
-3 + 5 : (-5) = -3 - 1 = -4
b)
(-6) * (-15 + 12) = -6 * (-3) = 18
3.
a)
(1,5)^7 : (1,5)^5 = 1,5² = 2,25
b)
(4/3)^4 * 3^4 = 4^4 : 3^4 * 3^4 = 4^4 = 256
c)
(5/7)^5 * (1 2/5)^6 = (7/5)^-5 * (7/5)^6 = 7/5 = 1 2/5
d)
49³ * 7³ : 7^8 = (7²)³ * 7³ : 7^8 = 7^6 * 7³ : 7^8 = 7^9 : 7^8 = 7^1 = 7
4.
√15 * √5 = √75
odp. D.
Szczegółowe wyjaśnienie: